Pemberdayaan Potensi PKK Cabawan Kota Tegal Melalui Pelatihan Pembatan Sabun Cair di Masa Pandemi Covid-19 - Heru Nurcahyo; Aldi Budi Riyanta; Joko Santoso (Jurnal Pengabdian UNDIKMA, 2021)
The aims of this community service is to provide assistance and training to the PKK for the manufacture of liquid soap products based on waste oil jelantah to improve the understanding and skill of the PKK through the manufacture of liquid soap preparation forms to take a role in breaking the spread of the Covid-19 outbreak and provide motivation for the development of the creative economy. This method of implementation uses training conducted for one month in December 2020 by starting to provide materials, make preparations and evaluation of preparations to result in good liquid soap. Then for the evaluation of participants by holding pretests and posttests to see the increase in participants' knowledge. The results of this activity obtained an increase in science and understanding of the manufacture of liquid soap by 21% regarding the understanding and knowledge that has been given.